(untitled) (Религиски дијалог и соработка, 2022)
The absolute and supreme authority of religion makes social andpoliticalnorms indisputable, which guarantees social stability. It is one of the three factors fortheunification of humanity, along with universal empires and universal payment (Харари,2016). There are three points in considering the relationship between religion and globalization.First, why does it resist the idea of globalism. Secondly, that unification will graduallylead to the construction of a new religion and hence to the abolition of religionitself. Andthird, today it is the only alternative to globalism, so it suffers the most powerful pressure(Косиченко, 2013). Following the Montreal Conference of the World Council of Churches (1963), therehasbeen a shift in emphasis from theology to anthropology or “fromGod to man”. But whichanthropology: the secular one, based on Bonhoeffer’s ill-quoted phrase that “thereis no God” or the theological one (according to Raner), which defines man not onlyaspsychologically, but also as a phenomenon impossible to explain without referencetoGod. This is important for modern ecumenical thinking, in which secular theories provedecisive. They try to derive categories that are valid for both the Christian andthesecularman (Майендорф, 2021). In the 21 st century, religious myths still divide people. With the progress of science, theyfail to explain the world – they do not bring rain, they do not cure diseases, theydonotproduce bombs. They set the boundaries of national identities (Харари, 2019). Buttheyalso give confidence that human happiness can be achieved in the mystical religiousexperience, which frees from the monotonous and inhuman determinismof theeconomyand other systems that regulate human life.